PENGARUH POLA ASUH SANTRI DI PONDOK PESANTREN MODERN DAAR EL ISTIQOMAH KELAS 8 TERHADAP PRESTASI BELAJAR - Abdul Fattah; Desty Endrawati; Meta Aprilia; Iin Fadilah; Nazmi Laila Gita (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research discusses the influence of modern Islamic boarding school parenting styles on the character formation of students. Modern Islamic boarding school parenting styles combine Islamic values with a structured formal education approach. This research uses qualitative methods with a case study approach at several modern Islamic boarding schools in Indonesia. The research results show that modern Islamic boarding school parenting styles play a significant role in shaping the character of students, such as independence, discipline, responsibility, and integrity. These values are instilled through daily activities that are integrated with religious education, academics, and life skills. Supporting factors include a conducive environment, the role of caregivers, and relevant curriculum support.